Podcasting or Teaching in An Alternative High School - Murphy, Jack (Radical Teacher, 2018)
Hello-- My name is Jack Murphy, and I am a high school English teacher in Chicago. My school is called Truman Middle College, an alternative high school for students 16-21 who have dropped out of public schools and are returning to earn their degree. I am writing both to express my appreciation for this journal, which I have found very useful and inspiring, and also to submit a proposal for 2 possible articles. I have two ideas I would like you to consider: one a short piece on a very successful project I have used in my class and another a longer piece on the nature of working at a school like mine. 1. Podcast assignment: a very interesting and successful project I have used in my English class several times now has been a podcast. Students decide whether they want to work on their own, in pairs, or in groups. Each group is challenged to create a podcast segment that connects to the theme Truman Middle College, a la This American Life. The broadness of this theme allows for practically endless variations-- from anodyne issues such as the school bathroom, commutes, and going to school with siblings to deeper issues such as inequality in the school system, student subjugation at the hands of school authority figures, and dealing with Chicago gun violence. The assignment is successful for several reasons, among them 1) student choice in topic 2) a fresh and interesting outlet for the skills and tools we have honed throughout the semester (interviewing, story telling, figurative language, etc), 3) technology such as garageband that students find engaging and useful outside of the classroom (creating the fabulous situation where certain students, often quiet or disengaged, become classroom experts in the program, volunteering to assist and teach others, including their teacher). 2. Teaching At An Alternative High School- This could be a longer reflection on the nature of teaching at a school like TMC. The students at my school have all been kicked out of another school, for a wide variety of reasons. We have students who have been incarcerated, students who have children of their own, students who work a fulltime low-wage job in addition to being a fulltime high school student, just to name a few obstacles they face. Our attendance is absolutely atrocious, students are often extremely bitter about schooling in general after a lifetime of bad experiences, and even the most dedicated are often too exhausted, hungry, or depressed to enjoy consistent success. It is at our little school you see the full tyranny of capitalism in full fury, as well as all the conflicting incentives and agendas imposed on teachers by CPS, the charter network, and the high-stakes testing regime. Much effort made by admin or teachers is often in pursuit of good data and other symbols of productivity, at the blatantexpense of the student population. It is my 5th year as a teacher at this school (and 8th in general, all spent in Chicago) and nothing has done more to radicalize my politics than seeing what these young people are forced to endure on a daily basis. Thank you for reading. If either of these ideas interest you, please let me know and I can produce the pieces.